Entrepreneurship and new product development: Exploring the "advantage of youth" and "business acumen" views. Issue 5 (19th May 2022) - Grilli, Luca
Abstract: We explore the relevance of two different views on new product development (NPD) drivers, defined as "advantage of youth" and "business acumen." The two arguments, that establish a negative relationship between an individual's age and NPD and a positive impact of professional experience on NPD, are theoretically contextualized and empirically tested in the entrepreneurship domain. Considering a sample of more than 4000 Italian entrepreneurs of innovative start‐ups, a series of econometric analyses confirm that both effects apply and reveal interesting nuances as to the relevance of the age effect and the relative importance of different dimensions of entrepreneurs' business acumen on NPD. Further additional analyses highlight how both the "advantage of youth" and "business acumen" do not necessarily lead to successful entrepreneurial NPD, but at the same time, they both are found to importantly characterize top performers among entrepreneurs engaging in NPD. Overall, this in‐depth analysis on entrepreneurial NPD and its drivers underlies the importance of a micro‐founded and individual‐based approach in the study of new product dynamics, and in doing so, it contributes to enrich the upper echelons perspective and related frameworks on innovation outcomes through entrepreneurship. By theorizing and documenting those personal demographic and human capital traits which are mostly associated with entrepreneurial NPD, a series of interesting implications quite naturally descend for several stakeholders: (prospective) entrepreneurs, managers who aim at nurturing an intrapreneurship culture within their companies and policy makers interested in increasing dynamic efficiency in the economic system through the launch of new products and services.